PENINGKATAN KEMAMPUAN MENGENAL ANGKA MELALUI PERMAINAN BENTUK GEOMETRI DASAR PADA ANAK USIA 4-5 TAHUN DI TK THEOBROMA II MUMBULSARI JEMBER - Rohmah, Siti Ainur; Ahmad Afandi; Syamsul Muarif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on a preliminary study, several issues related to the lack of number recognition skills in early childhood are caused by limited educational teaching aids, such as games provided to introduce children to numbers, activities focused solely on number recognition, children's worksheets, and whitebo Based on a preliminary study, several issues related to the lack of number recognition skills in early childhood are caused by limited educational teaching aids, such as games provided to introduce children to numbers, activities focused solely on number recognition, children's worksheets, and whiteboards. Based on these issues, this study was conducted to improve number recognition skills through basic geometric shapes.The objectives of this study were to determine: 1) Number recognition skills before implementing basic geometric shapes; 2) The process of implementing basic geometry to improve number recognition skills in each cycle; 3) Number recognition skills in group A of THEOBROMA II Kindergarten, Mumbulsari, Jember, after implementing games using basic geometric shapes in each cycle.This study is based on the premise that games using basic geometry can be used as educational teaching aids, and these games are an appropriate way to improve cognitive abilities in early childhood, especially in number recognition. Based on this assumption, the hypothesis is proposed that children's number recognition skills are expected to improve if the use of basic geometric shapes games in group A of THEOBROMA II Kindergarten, Mumbulsari, Jember, is implemented.This study used classroom action research. Data collection tools were observation and documentation. The data analysis techniques used were data reduction, data display, conclusions, and verification. The subjects or respondents in this study were 12 children from group A of THEOBROMA II Mumbulsari Kindergarten, Jember.ards. Based on these issues, this study was conducted to improve number recognition skills through basic geometric shapes.The objectives of this study were to determine: 1) Number recognition skills before implementing basic geometric shapes; 2) The process of implementing basic geometry to improve number recognition skills in each cycle; 3) Number recognition skills in group A of THEOBROMA II Kindergarten, Mumbulsari, Jember, after implementing games using basic geometric shapes in each cycle.This study is based on the premise that games using basic geometry can be used as educational teaching aids, and these games are an appropriate way to improve cognitive abilities in early childhood, especially in number recognition. Based on this assumption, the hypothesis is proposed that children's number recognition skills are expected to improve if the use of basic geometric shapes games in group A of THEOBROMA II Kindergarten, Mumbulsari, Jember, is implemented.This study used classroom action research. Data collection tools were observation and documentation. The data analysis techniques used were data reduction, data display, conclusions, and verification. The subjects or respondents in this study were 12 children from group A of THEOBROMA II Mumbulsari Kindergarten, Jember.